2010
DOI: 10.1021/ja106991f
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Dynamics of Hole Hopping in Extended DNA G-Tracts. An Unbiased Random Walk

Abstract: We report the measurement of distance- and temperature-dependent rate constants for charge separation in capped hairpins in which a stilbene hole acceptor and hole donor are separated by A(3)G(n) diblock polypurine sequences consisting of 3 adenines and 1-19 guanines. The longer diblock systems obey the simplest model for an unbiased random walk, providing a direct measurement of k(hop) = 4.3 × 10(9) s(-1) for a single reversible G-to-G hole hopping step, somewhat faster than the value of 1.2 × 10(9) s(-1) cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 38 publications
13
106
0
Order By: Relevance
“…An average activation energy of 326 ± 6 meV was observed for T17-A monolayers. A similar value for E A was also found for T17, which is higher than previously reported for Nile blue monolayers 26,28 and similar constructs, 34,47,48 but closer to theoretically anticipated values for CT through DNA. 49,50 Laviron analysis of the T17-A monolayer was also performed and found to give similar rate results (see Supporting Information Figure 4).…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…An average activation energy of 326 ± 6 meV was observed for T17-A monolayers. A similar value for E A was also found for T17, which is higher than previously reported for Nile blue monolayers 26,28 and similar constructs, 34,47,48 but closer to theoretically anticipated values for CT through DNA. 49,50 Laviron analysis of the T17-A monolayer was also performed and found to give similar rate results (see Supporting Information Figure 4).…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…In the SH simulations of hole transfer in AAAA, the wave function of the hole remains localized to a single A for most of the time, which is the same appearance that is observed in BO simulations. The rate of next-neighbour hole transfer can be determined in such a case and amounts to ca 100 ns -1 , which is roughly an order of magnitude larger than the experimental estimates [101,102]. This discrepancy may be caused by the preliminary character of the SH implementation, which seems to require additional attention regarding the calculation of hopping probabilities and decoherence behaviour.…”
Section: Mfmentioning
confidence: 84%
“…As described above, Lewis et al reported that the single-step hopping rate of HT was 4.3 × 10 9 and 1.2 × 10 9 s –1 for G-to-G and A-to-A, respectively. 19 Our research group found that the A-to-A hopping rate was 2 × 10 10 s –1 . 58 Therefore, it became clear that the hopping rate of the excess electron among consecutive T's is faster than the hole hopping rate among A's and G's.…”
Section: Excess Electron Transfer In Dnamentioning
confidence: 88%
“…Recently, Lewis and co-workers estimated the A-to-A and G-to-G hopping rates to be 1.2 × 10 9 and 4.3 × 10 9 s –1 , respectively, based on the direct observation of HT dynamics in a photosensitizing acceptor–DNA–donor system by transient absorption spectroscopy. 19 Thus, it can be concluded that the single step hole hopping time in A's or G's is on the order of several tens to hundreds of picoseconds.…”
Section: Hole Transfer In Dnamentioning
confidence: 99%